Photoluminescent core-shell particles of organic dye in silica - Ethiraj, Anita S.; Hebalkar, Neha; Kharrazi, Sharmin; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Journal of Luminescence, 2005)
Using a single silica precursor, Rhodamine 6G organic dye molecules have been entrapped in silica particles resulting into core-shell particles of similar to 500 nm diameter. Energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy analysis reveals that dye molecules are trapped inside the silica particles. Photoluminescence investigations show that highly luminescent and photostable core-shell particles are formed. Such core-shell particles can be easily suspended in water and would be useful for a variety of applications. However, there is a blue shift in the photolumineseence wavelength in case of core-shell particles compared to bare dye powder sample. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: core-shell; Luminescence; Nanoparticles; photoemission; RH06G dye; tetraethylorthosilicate (TEOS)

Study of correlation of structural and surface properties with electrochemical behaviour in carbon aerogels - Hebalkar, Neha; Arabale, G.; Sainkar, S. R.; Pradhan, S. D.; Mulla, Imtiaz S.; Vijayamohanan, K.; Ayyub, P.; Kulkarni, S. K. (Journal of Materials Science, 2005)
Carbon aerogel is a promising material for electrochemical double layer capacitors. In this paper carbon aerogels prepared by subcritical drying method are investigated for the change in the structure and surface properties at different pyrolysis temperatures. The important relations between structure, morphology, surface area and electrical properties were studied using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), surface area measurement and cyclic voltametry. It is shown that structure and the surface functional groups play important role in enhancement of electrochemical capacitance. The specific capacitance achieved was 114 F/gm which is quite large value for subcritically prepared carbon aerogels without any kind of activation process. (c) 2005 Springer Science + Business Media, Inc.

Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide

Thermally assisted semiconductor-like to insulator transition in gold-poly(methyl methacrylate) nanocomposites - Abyaneh, Majid Kazemian; Pasricha, Renu; Gosavi, S. W.; Kulkarni, S. K. (Nanotechnology, 2006)
Gold-polymethylmethacrylate ( PMMA) nanocomposites were fabricated by mixing gold nanoparticles capped with oleylamine in polymethylmethacrylate. The samples were analysed using UV-vis absorption spectroscopy, transmission electron microscopy, small angle x-ray scattering, Fourier transform infrared spectrometry ( FTIR) and x-ray photoelectron spectroscopy ( XPS). Electrical resistivity of nanocomposite samples was measured by a four-probe technique in the 70-300 K range. The nanocomposites showed a transition with an onset at similar to 160-165 K. They exhibited a semiconductor-like conductivity at higher temperatures and nearly temperature independent conductivity at lower temperatures. The interfacial interaction of Au nanoparticles and PMMA polymer is investigated using FTIR and XPS. A ligand-exchange process occurs when capped gold nanoparticles are incorporated in PMMA polymer.

Highly photostable dye entrapped core-shell particles - Ethiraj, Anita S.; Kharrazi, Sharmin; Hebalkar, Neha; Urban, J.; Sainkar, S. R.; Kulkarni, S. K. (Materials Letters, 2007)
Organic dye namely Coumarin 7 has been entrapped in silica particles using a single silica precursor viz. tetraethylorthosilicate. Both bare Coumarin 7 dye and dye incorporated core-shell particles were studied. Investigations of these core-shell composites were carried out using different characterization techniques such as energy dispersive X-ray analysis, X-ray photoelectron spectroscopy and transmission electron microscopy. It has been shown that the photostability of dye molecules is improved along with an increase in photoluminescence. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: core-shell; coumarin 7 dye; Luminescence; photostability; tetraethylorthosilicate

Low temperature synthesis and NOx sensing properties of nanostructured Al-doped ZnO - Navale, S. C.; Ravi, V.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2007)
Although ZnO is studied intensively as a sensing material, there are limited reports available on aluminum-doped ZnO (AZO) as a NO, sensor. This paper reports selective NO, sensing characteristics of M-doped ZnO synthesized in the form of porous pellets sintered at 350 degrees C. The salient feature of our experimental results is that our sensor can detect small concentrations of NO, at lower operating temperature. It is also observed that as compared to gases such as SOx HCl, LPG, H2S, H-2, ammonia, alcohol and acetone it selectively detects NOx due to Al-doping. The amount of Al in ZnO during synthesis is varied between 1 and 10 wt%. Our sensor senses NO, concentration as low as 20ppm at 100 degrees C with a %response of 11 and a %response of 740 at 300 degrees C for 1 wt% Al. Of all the compositions with Al-doping, I wt% is found to give best results. Sensing experiments carried out at 350 C, however. do not show any significant improvement in the gas sensing properties. The phase contents and lattice parameters were determined by XRD and the average particle size was obtained using Scherrer formula. A probable mechanism for sensing NO, involving oxygen ion adsorption and desorption on the surface of sensor has been suggested. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: aluminum doping; nanomaterial; NOx; Sensor; ZnO

Titania nanoparticles synthesis in mesoporous molecular sieve MCM-41 - Lihitkar, N. B.; Abyaneh, Majid Kazemian; Samuel, V.; Pasricha, R.; Gosavi, S. W.; Kulkarni, S. K. (Journal of Colloid and Interface Science, 2007)
Nanocrystalline titanium oxide (TiO2) is one of the most useful oxide material, because of its widespread applications in photocatalysis, solar energy conversion, sensors and optoelectronics. The control of particle size and monodispersity of TiO2 nanoparticles is a challenging task. The use of MCM-41, an inorganic template of uniform pore size (2-10 nm), can overcome this difficulty and produce stable nanoparticles of uniform size and shape. Here, we demonstrate the synthesis of titania nanoparticles inside the pores of silica based MCM-41 forming a TiO2/Si-MCM composite. Composites are formed in the alcoholic medium by incipient wetness impregnation method. Titania particles of average 3 nm size are obtained. Effect of silica and titania precursors on the quality of nanoparticles has been investigated. The characterization of titania-MCM-41 composites has been carried out using a variety of techniques like UV-vis absorption spectroscopy, X-ray diffraction, FT-IR spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy and photoluminescence spectroscopy. It has been found that the titania particles are co-ordinated with Si-MCM by Si-O-Ti covalent bond. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: incipient wetness impregnation; Mesoporous material; template; titania

EPR and DRS evidence for NO2 sensing in Al-doped ZnO - Navale, Shalaka C.; Ravi, V.; Srinivas, D.; Mulla, Imtiaz S.; Gosavi, S. W.; Kulkarni, S. K. (Sensors and Actuators B-Chemical, 2008)
Zinc oxide (ZnO) is a well-known semiconducting multifunctional material wherein properties right from the morphology to gas sensitivity can be tailor-made by doping or surface modification. Aluminum (Al)-incorporated porous zinc oxide (AI:ZnO) exhibits good response towards NO2 at low-operating temperature. The NO2 gas concentration as low as 20 ppm exhibits S = 17% for 5 wt. % Al-incorporated ZnO. The NO2 response increases with operating temperature and concentration and reaches to its maximum at 300 degrees C without any interference from other gases such as SO3, HCl, LPG and alcohol. Physico-chemical characterization likes differential thermogravimetric analysis (TG-DTA) electron paramagnetic resonance (EPR) and diffused reflectance spectroscopy (DRS) have been used to understand the sensing behavior for pure and A]-incorporated ZnO. The TG-DTA depicts formation of ZnO phase at 287 degrees C. The EPR study reveals distinct variation for O- (g=2.003) and Zn interstitial (g = 1.98) defect sites in pure and Al:ZnO. The DRS studies elucidate signature of adsorbed NO, species in aluminium-incorporated zinc oxide indicating its tendency to adsorb these species even at low temperatures. This paper is an attempt to correlate the gas sensing behavior with the physico-chemical studies such as EPR and DRS. (c) 2007 Published by Elsevier B.V.
Keywords: aluminum doping; DRS; EPR; NO2 sensor; ZnO

Low temperature synthesis of ZnSe nanoparticles - Deshpande, Aparna; Singh, Shashi B.; Abyaneh, Majid Kazemian; Pasricha, Renu; Kulkarni, S. K. (Materials Letters, 2008)
Synthesis of thioglycerol capped zinc selenide nanoparticles with a relatively narrow size distribution by a simple and inexpensive low temperature (similar to 80 degrees C) wet chemical method is reported here. Main advantage of this method is the use of non-toxic precursors. The size of the nanoparticles can be varied easily by changing the concentration of the capping agent. The extracted nanoparticles remain stable under normal atmospheric conditions and can be redispersed in suitable solvents. The sharp absorption features obtained in the UV-Visible absorption spectra reveal the formation of monodispersed ZnSe nanoparticles. The nanoparticles were characterized using X-ray photoelectron spectroscopy, X-ray diffraction, UV-Visible absorption spectroscopy, photoluminescence and transmission electron microscopy. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanomaterials; Semiconductor; X-ray techniques

Optical investigations of interaction between zinc tetra phenyl porphyrin and CdSe nanoparticles - Lihitkar, N. B.; Singh, S. B.; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Chemical Physics Letters, 2009)
Interactions between nanoparticles of zinc tetra phenyl porphyrin (ZnTPP) with CdSe nanoparticles in dimethyl sulphoxide solvent have been investigated. A ZnTPP-CdSe complex was formed which showed substantial changes in the UV-Vis absorption spectra in the presence of CdSe. Fluorescence measurements showed an interesting behavior at low as well as high concentrations of CdSe. When low concentrations of CdSe nanoparticles were added to the ZnTPP nanoparticles solution, besides two fluorescence bands due to ZnTPP nanoparticles, an intense new band appeared. On the other hand at high concentrations of CdSe one of the fluorescence band of ZnTPP at similar to 604 nm increased. (C) 2009 Published by Elsevier B. V.

Investigations of magnetic and dielectric properties of cupric oxide nanoparticles - Bhalerao-Panajkar, Rohini S.; Shirolkar, Mandar M.; Das, Raja; Maity, Tuhin; Poddar, Pankaj; Kulkarni, S. K. (Solid State Communications, 2011)
Cupric oxide nanoparticles of similar to 8-10 nm width and 40-45 nm length self assembled as large particles similar to 1-1 5 mu m have been investigated in the 10-325 K temperature range using magnetic and dielectric measurements In magnetic measurements a single broad peak at similar to 230 K in a zero field cooled sample has been observed Coercivity in magnetization measurements at 10 K suggests that the nanoparticles are core-shell type particles with an antiferromagnetic core and a ferromagnetic shell Dielectric measurements at various frequencies from 3 7 Hz to 949 kHz exhibit a sharp peak at 284 K followed by weak anomalies around 213 and 230 K (C) 2010 Elsevier Ltd All rights reserved
Keywords: CuO nanoparticles; Dielectric; Ferroelectric transition; Ferromagnetic

Confinement of zinc oxide nanoparticles in ordered mesoporous silica MCM-41 - Lihitkar, P. B.; Violet, Samuel; Shirolkar, Mandar; Singh, Jai; Srivastava, O. N.; Naik, R. H.; Kulkarni, S. K. (Materials Chemistry and Physics, 2012)
Mesoporous silica (MS) and zinc loaded MS composites have been synthesized and characterized using high resolution transmission electron microscopy, X-ray diffraction, UV-visible spectroscopy, photoluminescence spectroscopy, N-2 adsorption-desorption isotherms, X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy. Thermal treatment of the zinc loaded MS composite lead to the formation of ZnO-MS composite. The well ordered uniform pore structure of MS (pore size similar to 3.4 nm) is found to remain stable even after 30% Zn loading albeit decrease in the pore size 1.2 nm indicates the formation of ZnO inside the pores. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Defect; Energy spectroscopy for chemical analysis (ESCA); Mesoporous; Photoluminescence spectroscopy; Surface properties